A Principal's Perspective. Issue 1 (September 2017) - Bouman, Tim
Based on my experiences as a teacher, administrator, and now principal of North Lawndale College Prep Charter School, this article describes how our school nurtures students and prepares them to succeed not only in high school but also in college, despite the challenges that they face as young people in the inner city. Located on the West Side of Chicago, Illinois, the mission of North Lawndale is clear: "To prepare young people from under-resourced communities for graduation from high school with the academic skills and personal resilience necessary for successful completion of college."